A phase 3, open‐label study of daclatasvir plus asunaprevir in Asian patients with chronic hepatitis C virus genotype 1b infection who are ineligible for or intolerant to interferon alfa therapies with or without ribavirin. Issue 11 (November 2016) - Wei, Lai; Zhang, Mingxiang; Xu, Min; Chuang, Wan‐Long; Lu, Wei; Xie, Wen; Jia, Zhansheng; Gong, Guozhong; Li, Yueqi; Bae, Si Hyun; Yang, Yong‐Feng; Xie, Qing; et al.
Abstract: Background and Aim: Daclatasvir plus asunaprevir has demonstrated efficacy and safety in patients with chronic hepatitis C virus genotype 1b infection. This study focused on evaluating daclatasvir plus asunaprevir in interferon (±ribavirin)‐ineligible or ‐intolerant Asian patients with genotype 1b infection from mainland China, Korea, and Taiwan. Methods: Interferon (±ribavirin)‐ineligible and ‐intolerant patients with genotype 1b infection received daclatasvir 60 mg tablets once daily plus asunaprevir 100 mg soft capsules twice daily for 24 weeks. The primary endpoint was sustained virologic response at post‐treatment week 24 (SVR24). Results: Of the 159 patients treated, 89.3% were Chinese, 65.4% were female, and 73.6% were interferon‐intolerant. Cirrhosis was present in 32.7% of patients, and 40.3% had IL28B non‐CC genotypes. SVR24 was achieved by 145/159 (91.2%) patients (100% concordance with SVR12) and was similarly high in cirrhotic patients (47/52, 90.4%). SVR24 was higher in patients without baseline NS5A (L31M or Y93H) resistance‐associated variants (RAVs) (137/139, 98.6%), including those with cirrhosis (43/44, 97.7%). Prevalence of baseline NS5A RAVs was low (19/159, 11.9%), particularly in mainland China (10/127, 7.9%). One death (0.6%), five serious adverse events (3.1%), and three grade 4 laboratory abnormalities (1.9%) occurred on treatment; none were considered related to study drugs. Two patients (1.3%) discontinued because of adverse events. Treatment was generally well tolerated regardless of cirrhosis status. Conclusions: Daclatasvir plus asunaprevir achieved a SVR24 rate of 91.2%, rising to 98.6% in patients without baseline NS5A RAVs, and was generally well tolerated in interferon (±ribavirin)‐ineligible or ‐intolerant patients with genotype 1b infection from mainland China, Korea, and Taiwan.